Low-Dose Fluvoxamine Modulates Endocytic Trafficking of SARS-CoV-2 Spike Protein: A Potential Mechanism for Anti-COVID-19 Protection by Antidepressants - Glebov, Oleg O. (Frontiers in Pharmacology, 2021)
Commonly prescribed antidepressants may be associated with protection against severe COVID-19, with one drug (fluvoxamine) currently undergoing a Phase 3 clinical trial. The mechanism of their action, however, remains unknown. Here, I investigated the effect of fluvoxamine on membrane trafficking of the SARS-CoV-2 spike protein and its cell host receptor ACE2 in HEK293T cells. A sub-therapeutic concentration (80 nM) of fluvoxamine rapidly upregulated fluid-phase endocytosis, resulting in enhanced accumulation of the spike-ACE2 complex in enlarged early endosomes. Diversion of endosomal trafficking may provide a simple cell biological mechanism consistent with the protective effect of antidepressants against COVID-19, highlighting their therapeutic and prophylactic potential.